Feasibility of a Lifestyle Intervention Program for Prevention of Diabetes Among Women With Prior Gestational Diabetes Mellitus (LIVING Study) in South Asia: A Formative Research Study - Tewari, Abha; Praveen, Devarsetty; Madhira, Pavitra; Josyula, Lakshmi K.; Joshi, Rohina; Kokku, Suresh B.; Garg, Vandana; Rawal, Ishita; Chopra, Kanika; Chakma, Nantu; Ahmed, Sabrina; Pathmeswaran, Arunasalam; et al. (Frontiers in Global Women's Health, 2020)
Aim: To refine and contextually adapt a postpartum lifestyle intervention for prevention of type 2 diabetes mellitus (T2DM) in women with prior gestational diabetes mellitus (GDM) in Bangladesh, India, and Sri Lanka. Materials and Methods: In-depth interviews (IDIs) and focus group discussions (FGDs) were conducted with women with current diagnosis of GDM, and health care professionals involved in their management, to understand relevant local contextual factors for intervention optimisation and implementation. This paper describes facilitators and barriers as well as feedback from participants on how to improve the proposed intervention. These factors were grouped and interpreted along the axes of the three main determinants of behaviour–capability, opportunity, and motivation. IDIs and FGDs were digitally recorded, transcribed, and translated. Data-driven inductive thematic analysis was undertaken to identify and analyze patterns and themes. Results: Two interrelated themes emerged from the IDIs and FGDs: (i) The lifestyle intervention was acceptable and considered to have the potential to improve the existing model of care for women with GDM; and (ii) Certain barriers such as reduced priority of self-care, and adverse societal influences postpartum need to be addressed for the improvement of GDM care. Based on the feedback, the intervention was optimised by including messages for family members in the content of the intervention, providing options for both text and voice messages as reminders, and finalising the format of the intervention session delivery. Conclusion: This study highlights the importance of contextual factors in influencing postpartum care and support for women diagnosed with GDM in three South Asian countries. It indicates that although provision of postpartum care is complex, a group lifestyle intervention program is highly acceptable to women with GDM, as well as to health care professionals, at urban hospitals.